1982
DOI: 10.1111/j.1651-2227.1982.tb09439.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Amino Acids in Term Neonates After a Feed of Human Milk or Formula

Abstract: Human milk and formulas with different quantities and qualities of protein were compared by measuring sequential postprandial changes in total amino acids and glycine/valine ratios in plasma of 23 healthy term neonates who had previously been breast-fed ad libitum. At the mean age of 5.5 days the infants received from a bottle 1/36 of their body weight of banked human milk (true protein 0.8 g/100 ml), or formula (1.5 g/100 ml of protein, whey-to-casein ratio 60 : 40 (adapted) or 18 : 82 (non-adapted), or 3.0 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

1983
1983
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
2
7
0
1
Order By: Relevance
“…We found that alanine rose significantly, which is in good agreement with the results of Tikanoja et al (6). They found that alanine rose 60-120 min after the formula feed, which they explained as being mainly caused by the production of alanine from glucose in peripheral tissues.…”
Section: Discussionsupporting
confidence: 92%
“…We found that alanine rose significantly, which is in good agreement with the results of Tikanoja et al (6). They found that alanine rose 60-120 min after the formula feed, which they explained as being mainly caused by the production of alanine from glucose in peripheral tissues.…”
Section: Discussionsupporting
confidence: 92%
“…Human milk amino acids occur in proteins and peptides, as well as a small percentage in the form of free amino acids and glucosamine 3 (Table 4- Tikanoja et al 224 reported that postprandial changes in plasma amino acids in breastfed infants were proportional to dietary intake and were highest for the branched-chain amino acids. Proteins constitute 0.9% of the contents in human milk and range up to 20% in some rabbit species.…”
Section: Proteinsmentioning
confidence: 99%
“…Sua composição inclui a alfa-lactalbumina, a lactoferrina, a lisozima, a soroalbumina, as imunoglobulinas e a betalactoglobulina. A alfa-lactalbumina, que constitui cerca de 40% das proteínas do soro do leite humano, é necessária para o transporte de ferro e ainda para a síntese de lactose na glândula mamária 18 .…”
Section: Composição Protéicaunclassified